De-stressing race. Documenting 'The trauma of freedom' in post-apartheid South Africa; through the viewpoint of a black female born during the state of emergency (1985-1990) - Msimanga, Nondumiso (My University, 2012)
This study is as an examination into the everyday experience of Freedom in our democracy as a traumatic one. I outline my search as a Sartrean existential project, via the definitions of the key terms in the investigation: Race, Trauma, Freedom, Post-apartheid, South Africa, Black and Female. I make use of a practice-as-research mode of exploration through the methodology of Narrative Inquiry to discover the stories that give meaning to my being; as a free being. Through a critical reflection on the theatrical praxis, I draw meaning as to what it means to be a young Black woman in South Africa today. Freedom as a conceptual fact and the awareness thereof is outlined as the cause of the distress that has been termed the ‘Trauma of Freedom’. What this work reveals to me is the paradoxical optimism that is inherent within the ‘Trauma of Freedom.
M.A., Faculty of Humanities, University of the Witwatersrand, 2011